2016
DOI: 10.1177/0363546516646107
|View full text |Cite
|
Sign up to set email alerts
|

Structural Abnormalities on Magnetic Resonance Imaging in Patients With Patellofemoral Pain

Abstract: Structural abnormalities of the patellofemoral joint have been hypothesized as a factor in the pathogenesis of PFP, but the study findings suggest that structural abnormalities of the patellofemoral joint on MRI are not associated with PFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 34 publications
0
36
1
1
Order By: Relevance
“…Osteophytes were also prevalent in this cohort (62%). BMLs were less prevalent in this study (39%) yet are common even in young asymptomatic knees 48 and can fluctuate over relatively short time periods 49 and thus may not represent a stable indicator of disease state. While we did not report reference values using these other structural features, we did evaluate them as secondary outcomes, and found similar dose-response patterns with thresholds suggesting a similar but somewhat weaker association than full thickness cartilage damage (Table 3, Supplementary tables 2 and 3).…”
Section: Discussioncontrasting
confidence: 59%
“…Osteophytes were also prevalent in this cohort (62%). BMLs were less prevalent in this study (39%) yet are common even in young asymptomatic knees 48 and can fluctuate over relatively short time periods 49 and thus may not represent a stable indicator of disease state. While we did not report reference values using these other structural features, we did evaluate them as secondary outcomes, and found similar dose-response patterns with thresholds suggesting a similar but somewhat weaker association than full thickness cartilage damage (Table 3, Supplementary tables 2 and 3).…”
Section: Discussioncontrasting
confidence: 59%
“…7 In a recent study, several novel magnetic resonance imaging (MRI) techniques were applied to gain more insight in the etiology of PFP. 8 Although it was long believed that PFP was caused by chondromalacia, 9 van der Heijden et al showed that structural abnormalities (eg, cartilage loss and osteophytes) seen on MRI are not associated with the presence of PFP. 8,10 Additionally, no differences in cartilage composition were seen between groups.…”
Section: Introductionmentioning
confidence: 99%
“…8 Although it was long believed that PFP was caused by chondromalacia, 9 van der Heijden et al showed that structural abnormalities (eg, cartilage loss and osteophytes) seen on MRI are not associated with the presence of PFP. 8,10 Additionally, no differences in cartilage composition were seen between groups. 11 However, in another study, significantly higher T1ρ relaxation times in lateral patellar cartilage were found in a group of maltracking (eg, patellar tilt present) PFP patients compared with healthy controls, indicating an impaired biochemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study using 3 T magnetic resonance imaging (MRI) demonstrated that structural abnormalities of the patellofemoral cartilage are not associated with PFP 9. In this study, minor patellar cartilage defects or patellar bone marrow lesions were frequently seen in both PFP patients and subjects without PFP.…”
Section: Pfp Pathophysiology or Pathomechanicsmentioning
confidence: 52%
“…These observations show that PFP can affect patients with and without any structural damage to the patellofemoral joint (PFJ) 7. Structural damage that is sometimes associated with PFP includes chondral and osteochondral damage, osteoarthritis (OA), overuse injuries of the extensor apparatus (tendonitis and insertional tendinosis), and patellar instability 9. It has been recommended that patients with a history of dislocations or subluxations should be considered separately from other patients with PFP because this subgroup of patients frequently have biomechanical risk factors that require different treatment approaches 1.…”
Section: Introductionmentioning
confidence: 97%